"There's so much they don't cover:" Limitations of healthcare coverage for Indigenous women in a non-federally recognized tribe - Jessica L. Liddell; Jenn M. Lilly (Elsevier, 2022)
Access to healthcare is an essential component in addressing health disparities. However, the limitations of insurance coverage, and other barriers in paying for and accessing healthcare have seldom been researched for Indigenous peoples. In addition, state recognized tribes do not have access to the healthcare services provided by the Indian Health Service, and there is a need for research documenting their unique healthcare needs. Qualitative description was used to conduct 31 semi-structured interviews with women from an Indigenous tribe in the Gulf South to understand their experiences in paying for healthcare services. Participants described: (1) Discrimination Based on Perceived Ability to Pay for Healthcare; and (2) Limitations of Healthcare Coverage, with sub-themes (a) Difficulties Understanding Coverage Limitations; (b) Inadequate Coverage; and (c) Limited Choice of Providers. These findings indicate that state-recognized tribal members may need specialized insurance programs, and more comprehensive coverage of healthcare services and medications. Future actions should promote tribal sovereignty and increase access to healthcare resources for state-recognized tribes.